Interleucina-17 em pacientes com doença renal crônica - Paula, Florange Licelot Campusano (2018)
Interleukin-17A (IL-17A) plays an important role in the human immune system with its proinflammatory actions, agonist mediator of defenses in infections, is also associated with several autoimmune diseases and the imbalance of this cytokine is associated with many pathologies such as rheumatoid arthritis, hypertension and chronic kidney disease (DRC). The problem of CKD for public health is the disproportionate increase in cases in the last two decades, both because of its high incidence and prevalence, as well as its considerable morbidity and mortality rate and socioeconomic cost, making it a major challenge for medicine and the whole world. society in general. Thus, the objective of this study was to analyze and correlate conventional renal parameters such as urea, creatinine, albumin and glomerular filtration rate (GFR) with serum levels of interleukin-17A in patients diagnosed with CKD at different stages. The study included 71 patients diagnosed with CKD at stage 3, 4, 5 and 21 control cases. For the serum levels of renal factors, specific kits were used for each test using the semi-automatic spectrophotometer (Bioplus® 2000). The quantification of the cytokine was performed by a cytometer (FACScalibur, BD, USA) and the statistical differences were evaluated by the Statistical Package for the Social Sciences (SPSS), where values of P ≤ 0.05 were considered significant. The results of this study demonstrated that the serum level of IL-17A has a positive correlation with urea and creatinine. On the other hand, IL-17A has an inverse association with GFR and albumin. Interestingly, IL-17A still showed association with various renal parameters, even when variables including age, sex, hypertension and diabetes were removed. In view of the above, we can conclude that IL-17A has a strong correlation with the conventional renal parameters used in the diagnosis and evaluation of the progression of CKD. Therefore, we may suggest that this cytokine is closely associated with the progression of CKD and its related complications, and may be a useful biomarker in the diagnosis and prevention of CKD..